2012
DOI: 10.3892/ol.2012.621
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of epidermal growth factor receptor variation with disease progression and aggressiveness in colorectal cancer depends on tumor location

Abstract: Abstract. The role of epidermal growth factor receptor (EGFR) in colorectal cancer (CRC) prognosis remains unclear despite the recent development of anti-EGFR treatments for metastatic disease. The heterogeneity of CRC may account for this discrepancy; proximal and distal CRC has been found to be genetically and clinicopathologically different. The aim of this study was to investigate the effect of tumor location on the association of EGFR with the conventional prognostic indicators (stage and grade) in CRC. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Some studies [ 24 ] have revealed that EGFR-positive rectal cancer cells are more proliferative and infiltrative, which correlate with the TNM stage and LB metastasis, indicating that the high expression of EGFR is associated with the high invasiveness and metastasis of tumours. According to the statistical data reported in the current literature, there are relatively large differences in the expression rates of EGFR in RAC, reporting that the over-expression of EGFR was observed in 65–97% patients with RAC [ 25 , 26 ]. In the present study, we found an 80% positive expression rate of EGFR in the patients with RAC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [ 24 ] have revealed that EGFR-positive rectal cancer cells are more proliferative and infiltrative, which correlate with the TNM stage and LB metastasis, indicating that the high expression of EGFR is associated with the high invasiveness and metastasis of tumours. According to the statistical data reported in the current literature, there are relatively large differences in the expression rates of EGFR in RAC, reporting that the over-expression of EGFR was observed in 65–97% patients with RAC [ 25 , 26 ]. In the present study, we found an 80% positive expression rate of EGFR in the patients with RAC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also suggested that the disease biology is different between right- and left-sided colon cancers. 24 , 25 , 26 , 27 Microsatellite instability is more common in right-sided cancers, whereas chromosomal instability is more characteristic of left-sided cancers. 28 Many studies have found that patients with microsatellite instability tumors have a better prognosis and that DNA MMR status is an independent favorable predictor of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated significant gene expression differences between right and left colon cancers. 25 , 26 , 34 , 35 Glebov et al 25 found that more than 1000 genes were expressed differentially in adult ascending versus descending colon, with 165 genes showing >2-fold and 49 genes showing >3-fold difference in expression levels. Papagiorgis et al 26 reported that the pattern of EGFR expression varies with disease progression and aggressiveness in CRC depends on tumor location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , Rajendran Shanmugam Muthupalani 2,3 , Arvind Ramanathan 3 * phospho-tyrosine residues on the EGFR (pY1148, pY1086, pY1101) enable differential activation of a number of other proteins in response to EGF stimulation (Papagiorgis et al, 2012). ERK2 is the founding member of MAPK family, the activation of which is mediated via Ras/Raf/MEK kinase pathway (Arvind et al, 2005;Mahalingam et al, 2008).…”
Section: Senthilnathan Rajendranmentioning
confidence: 99%